Tanshinone IIA inhibits viral oncogene expression leading to apoptosis and inhibition of cervical cancer. Issue 2 (28th January 2015) - Munagala, Radha; Aqil, Farrukh; Jeyabalan, Jeyaprakash; Gupta, Ramesh C.
Abstract: Human papilloma virus (HPV) is the well-established etiological factor of cervical cancer. E6 and E7 oncoproteins expressed by HPV are known to inactivate tumor suppressor proteins p53 and pRb, respectively. Tanshinone IIA (Tan IIA) is a diterpenoid naphthoquinone found in the traditional Chinese medicine Danshen ( Salvia sp.). Tan IIA has been shown to possess anti-tumor activity against several cancer types. In this study we show that Tan IIA potently inhibited proliferation of the human cervical cancer CaSki, SiHa, HeLa and C33a cells. Mechanistically in HPV positive CaSki cells, Tan IIA was found to (i) downregulate expression of HPV E6 and E7 genes and modulate associated proteins E6AP and E2F1, (ii) cause S phase cell cycle arrest, (iii) induce accumulation of p53 and alter expression of p53-dependent targets, (iv) modulate pRb and related proteins, and (v) cause p53-mediated apoptosis by moderating Bcl2, Bax, caspase-3, and PARP cleavage expressions. In vivo, Tan IIA resulted in over 66% reduction in tumor volume of cervical cancer xenograft in athymic nude mice. Tan IIA treated tumor tissues had lower expression of proliferation marker PCNA and changes in apoptosis targets were in agreement with in vitro studies, further confirming reduced proliferation and involvement of multiple targets behind anti-cancer effects. This is the first demonstration of Tan IIA to possess significant anti-viral activity by repressing HPV oncogenes leading to inhibition of cervical cancer. Together, our data suggest that Tan IIA can be exploited as a potent therapeutic agent for the prevention and treatment of cervical and other HPV-related cancers.